Effects of Acupressure on Psychological Symptoms in Chronic Disease Patients: A Scoping Review - Hanifah Sahar Al Afra; Fitria Handayani; Meria Erawati (Indonesian Journal of Global Health Research, 2025)
Research related to the effects of acupressure on psychological problems in patients with chronic diseases has been conducted by previous researchers. However, so far reviews on this topic are still limited. The purpose of this review is to obtain an overview of the extent of the effects of acupressure on psychological symptoms of chronic disease sufferers based on the results of research that has been conducted. The method used is a scoping review, determining the research questions to be reviewed using the PICO (Population, Intervention, Comparison, Outcome) framework. The keywords used in the article search are "Acupressure" AND "Acupoints" AND "Psychological Symptoms" AND "Chronic disease" OR "Chronic ilness". Several databases used in this study such as Pubmed (n = 14), Science Direct (n = 495), Ebsco (n = 82), Proquest (n = 562), Scopus (n = 973) were then eliminated and screened into 10 articles studied. The review analysis was carried out using the Arksey and O'Malley theory approach. Based on the results of the analysis of 10 articles, it was found that acupressure has a positive effect in helping to reduce symptoms and improve the psychological condition of patients with chronic diseases, including relieving patient symptoms such as depression and anxiety in patients undergoing hemodialysis and breast cancer, reducing pain in osteoarthritis patients, overcoming insomnia which is often accompanied by anxiety disorders, emotional disorders (worry, nervousness, irritability), treating depression, anxiety, and insomnia in acute stroke patients, improving stress index, and sleep efficiency in the elderly with essential hypertension, reducing anxiety in female patients with coronary artery disease (CAD), decreasing the average stress score and improving the quality of life in patients with type 2 diabetes mellitus, increasing the quality of life and reducing emotional disorders in patients with polycystic ovary syndrome (PCOS). The conclusion of the journal review shows that acupressure has the effect of improving psychological conditions by reducing symptoms of anxiety, depression, stress, sleep disorders or insomnia and helping to improve the quality of life in patients with chronic diseases.